Gamification of Decentralized Ledger for Credit Card Application using Blockchain - Rohmat Taufiq; Agung Trisetyarso; Wayan Suparta; Bachtiar Saleh Abbas (Journal of Games, Game Art, and Gamification, 2019)
We propose a credit card application using blockchain to improve the approval, transparency and security process. Some studies explain the use of blockchain technology in credit card applications but have not described the concept and architecture. Therefore, this study describes and describes the architecture of using credit cards for credit card applications. The motivation of this research is to explain the implementation of blockchain technology, especially the decentralization process of ledgers in credit card applications. Next, we propose architecture and algorithms for credit card applications using blockchain. The conclusion in this study is a decentralized ledger for credit card applications that allows peer-to-peer transactions, decentralized credit card applications that are not bound by geographical boundaries, have two advantages for debtors and the banking industry. In addition, the architecture is made using a credit card for application credit cards and an explanation of how the architecture works.